Application of novel quantitative techniques for fluorodeoxyglucose positron emission tomography/computed tomography in patients with non‐small‐cell lung cancer. Issue 4 (23rd August 2016) - Wang, Duo; Koh, Eng‐Siew; Descallar, Joseph; Pramana, Ariyanto; Vinod, Shalini K; Ho Shon, Ivan
Abstract: Aim: Flurodeoxyglucose positron emission tomography/computed tomography (FDG‐PET/CT) is routinely used in non‐small‐cell lung cancer. This study aims to assess the prognostic value of quantitative FDG‐PET/CT parameters including standard uptake value (SUV), metabolic tumor volume (MTV) and total lesional glycolysis (TLG) in non‐small‐cell lung cancer. Methods: A retrospective review of 92 nonsurgical patients with pathologically confirmed stage I–III non‐small‐cell lung cancers treated with radical dose radiotherapy (≥50 Gy) was conducted. Metabolically active tumor regions on FDG‐PET/CT scans were contoured manually. SUV, MTV and TLG were calculated for primary, nodal and whole‐body disease. Univariate and multivariate (adjusting for age, sex, disease stage and primary tumor size in centimeters) Cox regression modeling were performed to assess the association between these parameters and both overall and progression‐free survival (PFS). Results: On univariate analysis, overall survival (OS) was significantly associated with primary MTV ( P = 0.03), whole‐body MTV ( P = 0.02), whole‐body maximum SUV ( P = 0.05) and whole‐body TLG ( P = 0.03). PFS was significantly associated with primary MTV ( P = 0.01), primary TLG ( P = 0.04), whole‐body MTV ( P < 0.01) and whole‐body TLG ( P = 0.01). On multivariate analysis, OS was significantly associated with whole‐body MTV ( P = 0.05). PFS was significantly associated with whole‐body MTV ( P = 0.02) and whole‐body TLG ( P = 0.05). Conclusions: Whole‐body MTV was significantly associated with overall and PFS, and whole‐body TLG was significantly associated with PFS on multivariate analysis. These two parameters may be significant prognostic factors independent of other factors such as stage. SUV was not significantly associated with survival on multivariate analysis.